Testing The Marshall-Lerner Condition on Indonesia's Trade Balance with The Five Biggest Trading Partners - Celvin Hamid, Muhammad; Nirmala, Tiara; Awaluddin, Imam (International Journal of Social Science, Education, Communication and Economics, 2024)
The Marshall-Lerner Condition is a theory that a trade balance deficit can be eliminated through currency depreciation, if in the long term the absolute number of long-term export and import demand elasticities is greater than one. Initially, exchange rate depreciation will have a negative impact on trade through two methods, namely changes in volume and changes in value. This study aims to test whether the Marshall-Lerner Condition fulfilled in Indonesia's bilateral trade balance with the five largest trading partners using the Ordinary Least Squares method and in the observation period 2010.1-2022.12. The results of the Marshall-Lerner Condition study that one of Indonesia's five largest trading partners, namely China, the Marshall-Lerner Condition is met. While for Indonesia's other four largest trading partners, namely Japan, the US, the European Union and Singapore, Indonesia's largest trading partners are uncertain whether they meet the Marshall-Lerner Condition or not.